2020
DOI: 10.1002/adhm.202001056
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Polyelectrolyte Graft Copolymers Enhance the Activity of Cyclic Dinucleotide STING Agonists

Abstract: Cyclic dinucleotide (CDN) agonists of stimulator of interferon genes (STING) hold great therapeutic potential, but their activity is hindered by poor drug‐like properties that restrict cytosolic bioavailability. Here, this challenge is addressed through the synthesis and evaluation of a novel series of PEGMA‐co‐DEAEMA‐co‐BMA copolymers with pH‐responsive, membrane‐destabilizing activity to enhance intracellular delivery of the CDN, cGAMP. Copolymers are synthesized with PEGMA of two different molecular weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Such advanced applications are advantageous for the coadministration of STING agonists with other PRRs to generate synergistic activation by a single construct. 6 , 111 Similar strategies for the (co)delivery of STING agonists have been employed by others, 112 116 and more advanced formulations are expected to emerge as the STING receptor is better understood.…”
Section: Synthetic Polymers With Innate Immunostimulatory Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…Such advanced applications are advantageous for the coadministration of STING agonists with other PRRs to generate synergistic activation by a single construct. 6 , 111 Similar strategies for the (co)delivery of STING agonists have been employed by others, 112 116 and more advanced formulations are expected to emerge as the STING receptor is better understood.…”
Section: Synthetic Polymers With Innate Immunostimulatory Activitymentioning
confidence: 88%
“…Using the PEG-Q11R9-CDN complexes, they could achieve selective delivery of the STING agonists to dendritic cells and subsequent activation in mice using a sublingual route of administration. Such advanced applications are advantageous for the coadministration of STING agonists with other PRRs to generate synergistic activation by a single construct. , Similar strategies for the (co)­delivery of STING agonists have been employed by others, and more advanced formulations are expected to emerge as the STING receptor is better understood.…”
Section: Synthetic Polymers With Innate Immunostimulatory Activitymentioning
confidence: 96%
“…Following endosomal acidification, the DEAEMA groups became protonated resulting in solubilization of the second block, disassembly of the nanoparticle, and exposure of the membrane-lytic DEAEMA-co-BMA domains, resulting in interactions with and the disruption of the endosomal membrane due to electrostatic attraction, resulting in disruption of the endosomal membrane. 12,31 A library of polymers was synthesized to examine the effect of second block molecular weight (MW) on the properties of the resultant nanoparticles while first block MW was held constant at 2 kDa, as it has been reported that polymer hydrophilic mass fraction affects nanoparticle self-assembly as well as endosomolytic capacity. Note: For the remainder of the paper, a PEG2k-EB'x'k copolymer will refer to a copolymer with a [DEAEMA-co-BMA] (E-co-B) block molecular weight of 'x' kDa.…”
Section: Polymer Characterizationmentioning
confidence: 99%
“…[5][6][7][8][9][10] Previously, our laboratory has described several classes of STING-activating nanoparticles (STANs). [11][12][13] STANs are composed of the pH-responsive, endosomolytic diblock copolymer poly[(ethylene glycol)x-block-[((2-diethylamino) ethyl methacrylate)0.6-co-(butyl methacrylate)0.4]y (PEG-b-DEAEMA-co-BMA), and exploit the aforementioned mechanism to induce disruption of the endosomal membrane for the cytosolic delivery of cyclic dinucleotides (CDNs), which are agonists of the stimulator of interferon genes (STING) pathway. 11,12 The STING pathway is triggered when the enzyme cyclic-GMP-AMP synthase (cGAS) detects DNA in the cytoplasm, a common indicator of viral infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation